A comprehensive review on energy efficient CO2 breakthrough technologies for sustainable green iron and steel manufacturing. (October 2015) - Quader, M. Abdul; Ahmed, Shamsuddin; Ghazilla, Raja Ariffin Raja; Ahmed, Shameem; Dahari, Mahidzal
Abstract: Iron and steel industry is the largest energy consuming manufacturing sector in the world. It is responsible for emitting 4–5% of the total anthropogenic CO2 . Due to consistently increasing demand of iron and steel products for human needs, fossil-fuel energy use and CO2 emission will continue to grow in this industry. So there is a strong motivation to develop and implement energy-efficient and low-carbon technologies as well as carbon reduction programs for this industry. Enhancing the development and deployment of high-temperature waste heat energy recovering technologies along a desired combination of carbon capture and storage (CCS) technologies will be the effective solution to reducing CO2 emissions from iron and steel production. The aim of this paper is to provide a comprehensive overview of the worldwide carbon reduction programs and new CO2 breakthrough technologies for energy saving and carbon capture and storage in iron and steel making processes by collating updated information from a wide range of sources. Also, a discussion on the selection of the appropriate technology and their barriers and stages of development and deployment is presented. It is found that lots of factors that limit the role of using biomass in CO2 abatement, so implementation of CCS technology in coal-based integrated steel plant would be an efficient means for sustainable green iron and steel manufacturing.